Report on regional learning platform webinar series - Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Programme for Climate-Smart Livestock Systems (PCSL) is an initiative designed to enable key actors in the livestock sector to increasingly include climate change adaptation and mitigation in their farming practices, sector strategies and investment projects. PCSL is financed by GIZ and commissioned by the Government of the Federal Republic of Germany. GIZ has commissioned the International Livestock Research Institute (ILRI) and the World Bank to implement the programme activities. ILRI’s programme activities are based in Kenya, Ethiopia and Uganda. One of the activities included the creation of national Learning Platforms for the purposes of information exchange and dissemination of research findings. Due to the Covid-19 pandemic and the resulting restrictions on travel and in-person gatherings, ILRI adjusted its plans for the national Learning Platforms. ILRI organized a series of three online meetings held with stakeholders from all three countries over a three-week period starting on 30th July 2020.